Mutation Spectrum of Familial Adenomatous Polyposis Patients in Turkish Population: Identification of 3 Novel APC Mutations - Arslan Ateş, Esra; Alavanda, Ceren; Demir, Şenol; Keklikkıran, Çağlayan; Attaallah, Wafi; Özdoğan, Osman Cavit; Güney, Ahmet İlter (Turkish Journal of Gastroenterology, 2022)
Background: Familial adenomatous polyposis (OMIM #175100) and MUTYH-associated polyposis (OMIM #608456) are rare cancerprone disorders characterized by hundreds of adenomatous polyps in the colon and rectum, which have a high probability of malignanttransformation. Attenuated familial adenomatous polyposis is a variant of familial adenomatous polyposis, which is a term used for thecondition in which patients have less than 100 colorectal polyps. Germline heterozygous Adenomatous polyposis coli (APC) and biallelic MUTYH (mutY DNA glycosylase) pathogenic variations are responsible for familial adenomatous polyposis and MUTYH-associatedpolyposis respectively. The aim of this study is to discuss the clinical manifestations of patients having pathogenic APC and MUTYHvariations.Methods: We included 27 probands who have more than 10 colonic polyps in this study. After evaluation of their clinical and family histories, the probands were screened for APC and MUTYH variations via next generation sequencing. The family members of the probandscarrying pathogenic variations were screened via Sanger sequencing.Results: Among 27 probands, pathogenic APC and MUTYH variations were detected in 3 and 6 probands respectively. In the APC gene,3 novel truncating variations (p.Leu360*, p.Leu1489Phefs*23, and p.Leu912*) were detected in 3 unrelated probands. In the MUTYHgene, only 2 distinct pathogenic variations were detected (p.Pro295Leu and p.Glu480del) in the homozygous or compound heterozygous state.Conclusion: In this study, molecular etiology was clarified in 9 familial polyposis patients. The p.Pro295Leu and p.Glu480del variationsseem to be common in the Turkish population and may be considered as a first-step genetic test in Turkish familial polyposis patientsshowing autosomal recessive inheritance. However more studies are needed to reveal the exact frequency of these variations.